2022
DOI: 10.1155/2022/8683671
|View full text |Cite
|
Sign up to set email alerts
|

Quizlet as a Learning Tool for Enhancing L2 Learners’ Lexical Retention: Should It be Used in Class or at Home?

Abstract: In the twenty-first century, with the evolution of technologies, teaching and learning practices, especially in second language acquisition, have taken a significant leap. Numerous applications and software have been created to facilitate and boost learners’ L2 vocabulary. The goal of this study is to examine the effectiveness of Quizlet in enhancing lexical retention of EFL students at a private institution in Vietnam in two learning modes: at home and in class. Eighty-nine university students participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The reason could be that learning via Quizlet was fun and enjoyable. This is evident through the interviews with students using Quizlet in previous studies, which demonstrated a positive outlook on Quizlet use [14,25,28,36]. One more possible explanation is due to the game-like design of the activities on this platform [15].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The reason could be that learning via Quizlet was fun and enjoyable. This is evident through the interviews with students using Quizlet in previous studies, which demonstrated a positive outlook on Quizlet use [14,25,28,36]. One more possible explanation is due to the game-like design of the activities on this platform [15].…”
Section: Discussionmentioning
confidence: 84%
“…In addition, teachers should instruct their students to learn vocabulary in small sets, with regular practice on Quizlet rather than trying to remember a long list of words over a short period of time. Despite its effectiveness, this learning tool should be utilized in moderation because frequent repetition may cause boredom [28,36]. Finally, when implementing technology in the classroom, teachers should observe their students' use of laptops and mobile phones.…”
Section: Discussionmentioning
confidence: 99%
“… Alastuey and Nemeth (2020) discussed the effects of Quizlet on vocabulary acquisition, highlighting the cognitive, affective, and motivational benefits for students creating their own learning material. However, Nguyen and Van Le (2022) pointed out the limited empirical research on the effectiveness of Quizlet, indicating a gap in the evidence. İnci (2020) reported that the use of the application in foreign language lessons improved learner engagement of learners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These findings align with the research by Körlü and Mede (2018) , which indicated that Quizlet had a positive impact on students’ performance and autonomy in vocabulary learning ( Körlü and Mede, 2018 ). Also, several studies have demonstrated the positive influence of Quizlet on student’s cognitive learning such as vocabulary learning and retention ( Barr, 2016 ; Özer and Koçoğlu, 2017 ; Ashcroft et al, 2018 ; Körlü and Mede, 2018 ; Sanosi, 2018 ; Andarab, 2019 ; Çinar and Ari, 2019 ; Toy, 2019 ; Arslan, 2020 ; Chaikovska and Zbaravska, 2020 ; Tanjung, 2020 ; Van et al, 2020 ; Akhshik, 2021 ; Aksel, 2021 ; Fursenko et al, 2021 ; Ho and Kawaguchi, 2021 ; Kurtoğlu, 2021 ; Setiawan and Putro, 2021 ; Atalan, 2022 ; Lin and Chen, 2022 ; Nguyen and Van Le, 2022 , 2023 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation